PENGEMBANGAN KREATIVITAS DAN JIWA KEWIRAUSAHAAN ANAK PADA MAKANAN KHAS DAERAH DI WILAYAH SELAPARANG KECAMATAN KOTA MATARAM - M. Chairul Anam; Baiq Sarlita Kartiani; Lalu Jasawandi; Mujiburrahman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Creativity is the ability possessed by every human being to be able to create something new. Creativity is the main foundation for entrepreneurship. An understanding of creativity and entrepreneurship must be instilled from a child to become a provision of knowledge in the face of global competition in the future. The children's lack of interest in developing creativity and the lack of knowledge about entrepreneurship are the reasons for the Community Service (PKM) activity held at SDN 18 Mataram, Selaparang, Mataram City. The purpose of this PKM activity is to develop creativity and understanding of entrepreneurship in elementary school children with the method of delivering material, a question and answer system and the practice of painting Pelecing which is expected to have a selling value. The results of this PKM activity showed that the participants were very enthusiastic about participating in paying attention to the material presented and enthusiastic in carrying out the practice of painting Pelecing with various decorations. This PKM activity is a place to apply knowledge that is beneficial to the surrounding environment, especially in the Selaparang area.